2023
DOI: 10.1021/acs.jpcc.3c03383
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Characterization of Electronic Metal–Support Interactions in Ceria-Supported Pt Particles

Pablo Castro-Latorre,
Konstantin M. Neyman,
Albert Bruix

Abstract: Electronic metal−support interactions affect the chemical and catalytic properties of metal particles supported on reducible metal oxides, but their characterization is challenging due to the complexity of the electronic structure of these systems. These interactions often involve different states with varying numbers and positions of strongly correlated d or f electrons and the corresponding polarons. In this work, we present an approach to characterize electronic metal− support interactions by means of compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Although photocatalysts with a hollow sphere structure efficiently promote water splitting reactions 4,[40][41][42][43][44][45] and CO 2 reduction, 46 the applicability of such catalysts towards photocatalytic SRM remains unclear. Here, hollow sphere-structured TiO 2 was selected as a representative photocatalyst and was loaded with Pt and Rh 2 O 3 as co-catalysts to promote H 2 O reduction and CH 4 oxidation reactions, respectively, because Pt particles in contact with an oxide like CeO 2 have special electronic and chemical properties, 47,48 enabling activation of CH 4 at temperatures below 500 K. 49 To elucidate the photocatalytic SRM reaction mechanism on hollow-structured TiO 2 , the wavelength and temperature dependence of the SRM activity was examined in combination with spectroscopic techniques, including electron-spin resonance (ESR) and photo-luminescence (PL) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Although photocatalysts with a hollow sphere structure efficiently promote water splitting reactions 4,[40][41][42][43][44][45] and CO 2 reduction, 46 the applicability of such catalysts towards photocatalytic SRM remains unclear. Here, hollow sphere-structured TiO 2 was selected as a representative photocatalyst and was loaded with Pt and Rh 2 O 3 as co-catalysts to promote H 2 O reduction and CH 4 oxidation reactions, respectively, because Pt particles in contact with an oxide like CeO 2 have special electronic and chemical properties, 47,48 enabling activation of CH 4 at temperatures below 500 K. 49 To elucidate the photocatalytic SRM reaction mechanism on hollow-structured TiO 2 , the wavelength and temperature dependence of the SRM activity was examined in combination with spectroscopic techniques, including electron-spin resonance (ESR) and photo-luminescence (PL) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, computational studies of Pt nanoparticles are less common in the literature. They usually disregard the support and focus on understanding finite-size effects and establishing d-band correlations for isolated nanoparticles. Recent works have begun to consider the dynamic structure of Pt nanoparticles supported on metal oxides and exposed to reactants by combining heuristically postulated cluster models, , structures resulting from global optimization, , and large nanoparticles derived from bulk or gas-phase structures. …”
Section: Introductionmentioning
confidence: 99%
“…Several DFT studies have reported on the structure and the stability of atomically dispersed Pt on both low‐index and high‐index stepped ceria surfaces 24–30 . Other authors have investigated the interaction of Pt clusters on this support 31–35 . Smaller systems, such as Pt dimers on CeO 2 (111) have been modeled at the DFT + U level.…”
Section: Introductionmentioning
confidence: 99%